Literacy Difficulties and Emotional and Behavior Disorders: Causes and Consequences. Issue 3 (3rd July 2018) - Hurry, Jane; Flouri, Eirini; Sylva, Kathy
Abstract: Background: There is a well-established association between literacy difficulties and emotional and behavior disorders (EBD). However, the scarcity of experimental studies means directions of causality are not clear. Aims: This study investigates causal relationships between literacy and EBD, and implications of co-morbidity for intervention. Sample and method: In the first year of a quasi-experimental study of 258 six-year-olds with reading difficulties: 87 received Phonological Training (PT), 81 received Reading Recovery (RR), and 90 in the control group received standard tuition. Children were followed up immediately post-intervention and four years later. Results: Immediately post-intervention, RR significantly improved children's literacy (Cohen's d = .89). Four years later both RR and PT had small effects on literacy (Cohen's d = .25 and .26 respectively). These effects provided the opportunity to test the hypothesis that literacy difficulties cause or exacerbate EBD. This hypothesis was not supported as neither intervention reduced EBD. There was an interaction between hyperactivity symptoms at baseline and the effectiveness of PT, with PT being effective for children with few or no symptoms but ineffective for those with symptoms. EBD did not moderate the effectiveness of RR. Conduct disorder and hyperactivity at baseline had negative effects on literacy progress. Conclusions: Literacy difficulties do not appear to be a cause of EBD but conduct disorder and hyperactivity exacerbate literacy difficulties. This may be due to EBD interfering with the effectiveness of instruction. If children have more than one problem they probably need more or different support.